2017
DOI: 10.7554/elife.26691
|View full text |Cite
|
Sign up to set email alerts
|

9Å structure of the COPI coat reveals that the Arf1 GTPase occupies two contrasting molecular environments

Abstract: COPI coated vesicles mediate trafficking within the Golgi apparatus and between the Golgi and the endoplasmic reticulum. Assembly of a COPI coated vesicle is initiated by the small GTPase Arf1 that recruits the coatomer complex to the membrane, triggering polymerization and budding. The vesicle uncoats before fusion with a target membrane. Coat components are structurally conserved between COPI and clathrin/adaptor proteins. Using cryo-electron tomography and subtomogram averaging, we determined the structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
164
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(171 citation statements)
references
References 84 publications
6
164
1
Order By: Relevance
“…There are experimental data that the membrane dissociation rate of Arf1 is more rapid than that of coatomer in living cells [20], indicating that coatomer remains on the membrane after GTP hydrolysis on Arf1. Furthermore, recent studies involving structural analyses have suggested that the binding site of -COP to Arf1•GTP might be transmitted to KDEL cargo receptor after GTP hydrolysis on Arf1 [21]. These studies support the model by which GTP hydrolysis on Arf is related to cargo sorting.…”
Section: Introductionsupporting
confidence: 71%
“…There are experimental data that the membrane dissociation rate of Arf1 is more rapid than that of coatomer in living cells [20], indicating that coatomer remains on the membrane after GTP hydrolysis on Arf1. Furthermore, recent studies involving structural analyses have suggested that the binding site of -COP to Arf1•GTP might be transmitted to KDEL cargo receptor after GTP hydrolysis on Arf1 [21]. These studies support the model by which GTP hydrolysis on Arf is related to cargo sorting.…”
Section: Introductionsupporting
confidence: 71%
“…It remains to be seen whether this interaction occurs in vivo with the full coat complex and the tail in the context of a membrane. Various structures of coatomer suggest there may be sufficient flexibility in δ‐COP and the COPI coat as a whole to accommodate for a direct interaction with the cytoplasmic tails . Another curiosity is that Wx(n1‐6)W/F motifs often feature amongst highly acidic stretches ; however, this does not appear to be the case for the motif in the tail of GalNAc‐T4.…”
Section: Cytoplasmic Tail Sorting Motifsmentioning
confidence: 99%
“…Residues in bold highlight a φ(K/R)XLX(K/R) motif corresponding to a d-COP/f1-COP consensus binding motif [63]. Highlighted residues correspond to a WX(n1-6)(W/F) motif shown to bind to d-COP [ structures of coatomer suggest there may be sufficient flexibility in d-COP and the COPI coat as a whole to accommodate for a direct interaction with the cytoplasmic tails [19,77,78]. Another curiosity is that Wx(n1-6) W/F motifs often feature amongst highly acidic stretches [65]; however, this does not appear to be the case for the motif in the tail of GalNAc-T4.…”
Section: Direct Interactions Between Enzymes and Coatomermentioning
confidence: 99%
“…Three mammalian ArfGAPs (ArfGAP1, ArfGAP2 and ArfGAP3) have been implicated in the regulation of COPI function (Weimer et al, 2008) and have been shown to interact with COPI-coated vesicles produced in vitro (Weimer et al, 2008;Yang et al, 2002). COPI catalyses the ArfGAP-dependent GTP hydrolysis of Arf1 (Ahmadian et al, 1997;Dodonova et al, 2017;Goldberg, 1999;Luo et al, 2009).…”
Section: Membrane Recruitment Of Copi and Associated Machinerymentioning
confidence: 99%